Menstrual Cup use among Nulliparous Women: Breaking Taboos and Empowering Communities - A Scoping Review - Surama Manjari Behera; Priyamadhaba Behera; Debkumar Pal; Poojitha Sushama Malla; Binod Kumar Patro; E. Venkata Rao (Indian Journal of Community Medicine)
Menstrual cups offer a more comfortable menstruation experience, reducing disruptions to daily activities. They are eco-friendly and more cost-effective than other menstrual products. Our aim of the study was to understand menstrual cup use among nulliparous female and identify the challenges for their adoption and continued usage. Database-specific search strategies were formulated for Ovid, PubMed, Scopus, and Embase by using keywords such as “vaginal cup,” “menstrual cup,” and “nulliparous.” The search was conducted on November 15, 2024, and eligible studies published till November 1, 2024 were searched. Various study designs were considered, while studies that did not mention the proportion of nulliparous females among menstrual cup users were excluded. Out of 40 identified records, 11 studies were included after screening. Studies involving nulliparous females from various regions, including Canada, the USA, India, Colombia, Zimbabwe, and Kenya, suggest that menstrual cups constitute a safe and comfortable option for menstrual hygiene management (MHM). Nulliparous females encounter unique obstacles such as limited awareness of their reproductive systems, fears and restrictions related to the unscientific concept of virginity, and limited accessibility to menstrual cups. These barriers are compounded by minimal technical and social support. Nulliparous females also face specific issues such as increased menstrual bleeding and loss of school or college hours, which can significantly be mitigated by using menstrual cups. Evidence suggests that menstrual cups can be a safe and comfortable option for MHM among nulliparous females. It is essential to debunk social myths and taboos, provide accessibility to menstrual cups, offer training, and build confidence in young females from menarche. Engaging multiple personnel at different levels and receiving supportive guidance from healthcare providers are critical steps to increase public awareness and acceptance of menstrual cups.